A Dynamic Study of Protein Secretion and Aggregation in the Secretory Pathway - Mossuto, Maria Francesca (Public Library of Science, 2014)
Precise coordination of protein biogenesis, traffic and homeostasis within the early secretory compartment (ESC) is key for cell physiology. As a consequence, disturbances in these processes underlie many genetic and chronic diseases. Dynamic imaging methods are needed to follow the fate of cargo proteins and their interactions with resident enzymes and folding assistants. Here we applied the Halotag labelling system to study the behavior of proteins with different fates and roles in ESC: a chaperone, an ERAD substrate and an aggregation-prone molecule. Exploiting the Halo property of binding covalently ligands labelled with different fluorochromes, we developed and performed non-radioactive pulse and chase assays to follow sequential waves of proteins in ESC, discriminating between young and old molecules at the single cell level. In this way, we could monitor secretion and degradation of ER proteins in living cells. We can also follow the biogenesis, growth, accumulation and movements of protein aggregates in the ESC. Our data show that protein deposits within ESC grow by sequential apposition of molecules up to a given size, after which novel seeds are detected. The possibility of using ligands with distinct optical and physical properties offers a novel possibility to dynamically follow the fate of proteins in the ESC.